SARTRE'O BURTŲ LAZDELĖ. NIHILISTINĖ VAIZDUOTĖS LAISVĖ IR FENOMENOLOGIJA. - Sabolius, Kristupas (Problems / Problemos, 2009)
In Husserl's writings on fantasy, one could already find references to an important aspect of its function, the one of the consciousness which, stimulated by the vision of its possibilities, opens the perspective of undetermined worlds. The latter topic is widely developed by Sartre. Imagination is the freedom of consciousness, this is the main idea of his Imaginaire. However, this freedom conceals a fundamental duplicity or even triplicity. As Sartre puts it, "the act of imagination is at the same time constituting, isolating and nihilating". Consequently, the nihilistic and imaginary structure is identified in all the phases of consciousness as the essential definition of the relationship of human being to the world. To pose the world as the world or to nihilate (néantir) it is the same thing. In the description of L'être et le Néant, consciousness finds Nothingness in its own sight which constitutes horizons and covers things with halos. It means that Nothingness enters the world together with the sight and is supposed to be considered as an intentionality functioning according to the coordinating logics of imagination.